Variabilidade genética do peso ao nascer e seleção para crescimento em bubalinos do estado do Pará, Brasil - AGUIAR, Juliana Flor de (Instituto Nacional de Pesquisas da Amazônia, 2015)
Birth weight is a performance parameter of great zootechnical importance for both meat and dairy production, as well as for breeding animals, mainly due to its relation to survival rate at weaning, and the weight of animals throughout their developmental and growth phases. Therefore, the objective of this work was to establish heritability estimates, as well as phenotypic and genetic trends of birth weight of water buffaloes from State of Pará, Brazil. Descriptive statistics were calculated and the Shapiro-Wilk Normality test was performed with a Statistical Analysis System package. Heritability estimates were established by Bayesian inference. BW was 36.6 kg in average. The statistical model considered sex, year of birth and breed composition of the animals as fixed effects, and animal, maternal and residual as random effects. Direct heritability was platykurtic (flattened) and with higher asymmetry, presenting a bimodal distribution with the first mode close to 0.10, and the second mode close to 0.30; the maternal heritability was trimodal, with peaks very close to 0.15, and another, less evident, close to 0.20. The direct genetic trend of birth weight was negative (-0.03kg year-1) and maternal genetic trend was close to zero (0.001kg ano-1), even though the phenotypic trend had been positive (0.156 kg year-1). There is genetic variability to be addressed in a breeding program, however, very little was done as far as selection for growth of water buffaloes in the State of Pará.